2022
DOI: 10.7555/jbr.36.20220006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different regional cerebral blood flow on white matter hyperintensity in CADASIL patients

Abstract: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an early-onset inherited small vessel disease. Decreased cerebral blood flow (CBF) may contribute to white matter hyperintensity (WMH) severity in CADASIL, but more evidence is needed to support this hypothesis. This study comprised six patients with CADASIL who harbored mutations in the coding sequence of NOTCH3 and twelve age-matched neurologically healthy controls. We collected clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Importantly, the WM lesions are not pathologically uniform conditions but rather diverse abnormalities in the brain [2] . Reduced cerebral blood flow (CBF) is a contributing factor to the development of WM lesions [3] . Furthermore, disruptions in the differentiation of oligodendrocyte precursor cells (OPCs) into mature oligodendrocytes also play a role in the formation of WM lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the WM lesions are not pathologically uniform conditions but rather diverse abnormalities in the brain [2] . Reduced cerebral blood flow (CBF) is a contributing factor to the development of WM lesions [3] . Furthermore, disruptions in the differentiation of oligodendrocyte precursor cells (OPCs) into mature oligodendrocytes also play a role in the formation of WM lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al reported a clinical study of six patients of CADASIL and twelve healthy controls, they found that the severity of hypoperfusion correlates with the white matter hyperintensity volume. It highlighted the mutual links between the elements of the glio-vascular unit (G-unit) [ 8 ] . We hope the readers find this special issue interesting and intriguing.…”
mentioning
confidence: 99%